The Violence of Neoliberalism - Victoria E. Collins, Dawn L. Rothe (2019)
This book examines the impact of neoliberalism on society, bringing to the forefront a discussion of violence and harm, the inherent inequalities of neoliberalism and the ways in which our everyday lives in the Global North reproduce and facilitate this violence and harm.